Readability of Cancer Clinical Trials Websites - Hillyer, Grace Clarke (Cancer Control, 2020)
Clinical trials are critically important for the development of new cancer treatments. According to recent estimates, however, clinical trial enrollment is only about 8%. Lack of patient understanding or awareness of clinical trials is one reason for the low rate of participation. The purpose of this observational study was to evaluate the readability of cancer clinical trial websites designed to educate the general public and patients about clinical trials. Nearly 90% of Americans use Google to search for health-related information. We conducted a Google Chrome Incognito search in 2018 using the keywords “cancer clinical trial” and “cancer clinical trials.” Content of the 100 cancer clinical trial websites was analyzed using an online readability panel consisting of Flesch-Kincaid Grade Level, Flesch Reading Ease, Gunning-Fog Index, Coleman-Liau Index, and Simple Measure of Gobbledygook scales. Reading level difficulty was assessed and compared between commercial versus non-commercial URL extensions. Content readability was found to be “difficult” (10.7 grade level). No significant difference in readability, overall, and between commercial and non-commercial URL extensions was found using 4/5 measures of readability; 90.9% of commercial versus 49.4% of non-commercial websites were written at a >10th grade (P = .013) using Gunning-Fog Index. Written cancer clinical trials content on the Internet is written at a reading level beyond the literacy capabilities of the average American reader. Improving readability to accommodate readers with basic literacy skills will provide an opportunity for greater comprehension that could potentially result in higher rates of clinical trial enrollment.